(untitled) (Research, Society and Development, 2023)
Aging is a natural process that causes various changes in the skin and facial tissues. Polydioxanone (PDO) threads have been used as a non-surgical option for facial rejuvenation. These threads are inserted into the skin and stimulate collagen production, promoting a lifting effect. There are different types of PDO yarns, each with specific characteristics. The procedure for inserting the PDO wires is minimally invasive and performed in the office under local anesthesia. However, there are contraindications, such as autoimmune diseases, pregnancy and the use of anticoagulants. Some complications may occur, such as hematoma and infection, but they are usually transient and disappear within a few days. It is important to perform the technique correctly to avoid complications, such as wire migration. Studies have shown positive results with the use of PDO threads, but further research is needed to assess its long-term effectiveness, especially in older people and those with greater facial flaccidity. This technique can be indicated as a complement to other facial rejuvenation approaches and is more suitable for patients with few wrinkles and mild sagging. Based on this, the aim of this article is to carry out a comprehensive review of the scientific literature on the use of PDO threads in orofacial harmonization. The article aims to provide a theoretical basis on the benefits, indications, application techniques and results obtained with these threads, in addition to evaluating the safety and efficacy of their use.